Doxorubicin plus dacarbazine, doxorubicin plus ifosfamide, or doxorubicin alone as a first‐line treatment for advanced leiomyosarcoma: A propensity score matching analysis from the European Organization for Research and Treatment of Cancer Soft Tissue and Bone Sarcoma Group. Issue 11 (4th March 2020) - D'Ambrosio, Lorenzo; Touati, Nathan; Blay, Jean‐Yves; Grignani, Giovanni; Flippot, Ronan; Czarnecka, Anna M.; Piperno‐Neumann, Sophie; Martin‐Broto, Javier; Sanfilippo, Roberta; Katz, Daniela; Duffaud, Florence; Vincenzi, Bruno; et al.
Abstract : Background: The optimal treatment for advanced leiomyosarcoma is still debated. Given histotype‐specific prospective controlled data lacking, this study retrospectively evaluated doxorubicin plus dacarbazine, doxorubicin plus ifosfamide, and doxorubicin alone as first‐line treatments for advanced/metastatic leiomyosarcoma treated at European Organization for Research and Treatment of Cancer Soft Tissue and Bone Sarcoma Group (EORTC‐STBSG) sites. Methods: The inclusion criteria were a confirmed histological diagnosis, treatment between January 2010 and December 2015, measurable disease (Response Evaluation Criteria in Solid Tumors 1.1), an Eastern Cooperative Oncology Group performance status ≤2, and an age ≥ 18 years. The endpoints were progression‐free survival (PFS), overall survival (OS), and overall response rate (ORR). PFS was analyzed with methods for interval‐censored data. Patients were matched according to their propensity scores, which were estimated with a logistic regression model accounting for histology, grade, age, sex, performance status, tumor site, and tumor extent. Results: Three hundred three patients from 18 EORTC‐STBSG sites were identified. One hundred seventeen (39%) received doxorubicin plus dacarbazine, 71 (23%) received doxorubicin plus ifosfamide, and 115 (38%) received doxorubicin. In the 2:1:2 propensity score–matched population (205 patients), the estimated median PFS was 9.2 months (95% confidence interval [CI], 5.2‐9.7 months), 8.2 months (95% CI, 5.2‐10.1 months), and 4.8 months (95% CI, 2.3‐6.0 months) with ORRs of 30.9%, 19.5%, and 25.6% for doxorubicin plus dacarbazine, doxorubicin plus ifosfamide, and doxorubicin alone, respectively. PFS was significantly longer with doxorubicin plus dacarbazine versus doxorubicin (hazard ratio [HR], 0.72; 95% CI, 0.52‐0.99). Doxorubicin plus dacarbazine was associated with longer OS (median, 36.8 months; 95% CI, 27.9‐47.2 months) in comparison with both doxorubicin plus ifosfamide (median, 21.9 months; 95% CI, 16.7‐33.4 months; HR, 0.65; 95% CI, 0.40‐1.06) and doxorubicin (median, 30.3 months; 95% CI, 21.0‐36.3 months; HR, 0.66; 95% CI, 0.43‐0.99). Adjusted analyses retained an effect for PFS but not for OS. None of the factors selected for multivariate analysis had a significant interaction with the received treatment for both PFS and OS. Conclusions: This is the largest retrospective study of first‐line treatment for advanced leiomyosarcoma. In the propensity score–matched population, doxorubicin and dacarbazine showed favorable activity in terms of both ORR and PFS and warrants further evaluation in prospective trials. Abstract : In this propensity score‐adjusted, multi‐institutional series, doxorubicin and dacarbazine show better outcomes for the first‐line treatment of advanced leiomyosarcoma and warrant further studies. This series represents a benchmark for the future development of trials for leiomyosarcoma.